Mortality and cancer incidence among underground uranium miners in the Czech Republic 1977–1992. Issue 8 (5th June 2019) - Kelly-Reif, Kaitlin; Sandler, Dale P; Shore, David; Schubauer-Berigan, Mary; Troester, Melissa A; Nylander-French, Leena; Richardson, David B
Abstract : Objectives: Uranium miners in Příbram, Czech Republic were exposed to low and moderate levels of radon gas and other hazards. It is unknown whether these hazards increase the risk of mortality or cancer incidence when compared with the general Czech population. Methods: A cohort of 16 434 male underground miners employed underground for at least 1 year between 1946 and 1976, and alive and residing in the Czech Republic in 1977, were followed for mortality and cancer incidence through 1992. We compared observed deaths and cancer incidence to expectation based on Czech rates. Standardised mortality ratios (SMRs), standardised incidence ratios (SIRs) and causal mortality ratios were calculated. Results: Underground workers in the Příbram mines had higher rates of death than expected due to all causes (SMR=1.23, 95% CI 1.20 to 1.27), all cancers (SMR=1.52, 95% CI 1.44 to 1.60), lung cancer (SMR=2.12, 95% CI 1.96 to 2.28) and extrathoracic cancer (SMR=1.41, 95% CI 1.15 to 1.77). Similar excess was observed in cancer incidence analyses, with the addition of stomach cancer (SIR=1.37, 95% CI 1.11 to 1.63), liver cancer (SIR=1.70, 95% CI 1.16 to 2.25) and rectal cancer (SIR=1.41, 95% CI 1.16 to 1.66). The SIR was elevated for all leukaemias (SIR=1.51, 95% CI 1.08 to 2.07) and for lymphatic and haematopoietic cancers combined (SIR=1.31, 95% CI 1.05 to 1.61), but results for specific subtypes were imprecise. Deaths due to hazardous mining conditions resulted in 0.33 person-years of life lost per miner. Conclusions: Occupational exposure to the Příbram mines resulted in excess cancers at several sites, including sites previously linked to radon and uranium exposure. Incidence analyses showed relative excess of several additional cancer subtypes.